Train Traffic as a Powerful Noise Source for Monitoring Active Faults With Seismic Interferometry. Issue 16 (26th August 2019) - Brenguier, F.; Boué, P.; Ben‐Zion, Y.; Vernon, F.; Johnson, C.W.; Mordret, A.; Coutant, O.; Share, P.‐E.; Beaucé, E.; Hollis, D.; Lecocq, T.
Abstract: Laboratory experiments report that detectable seismic velocity changes should occur in the vicinity of fault zones prior to earthquakes. However, operating permanent active seismic sources to monitor natural faults at seismogenic depth is found to be nearly impossible to achieve. We show that seismic noise generated by vehicle traffic, and especially heavy freight trains, can be turned into a powerful repetitive seismic source to continuously probe the Earth's crust at a few kilometers depth. Results of an exploratory seismic experiment in Southern California demonstrate that correlations of train‐generated seismic signals allow daily reconstruction of direct P body waves probing the San Jacinto Fault down to 4‐km depth. This new approach may facilitate monitoring most of the San Andreas Fault system using the railway and highway network of California. Plain Language Summary: Even though laboratory experiments report that they should be preceded by detectable precursors, earthquakes remain unpredictable. Indeed, contrary to the lab, scanning natural faults at a few kilometers depth where earthquakes initiate requires operating high‐energy seismic sources continuously in time, which is found to be nearly impossible. In this study, we show that large freight trains generate sufficient seismic energy to travel down to a few kilometers depth and be detected at tens of kilometers from railways. We demonstrate that we can turn this apparently random source of seismic signal into an impulsive virtual seismic source to monitor active faults. We finally estimate that this new approach can be used for monitoring most of the San Andreas Fault system using the railway and highway network of California. Key Points: Freight trains in Southern California are locally equivalent to a magnitude 2.2 earthquake every day We use train noise to reconstruct repetitive virtual sources of P waves crossing the San Jacinto Fault at 4‐km depth Predictions of train noise across California show potential for passive monitoring of most of the San Andreas Fault system